New synonyms and new species of European aquatic dance flies (Diptera, Empididae) - Wagner, Rüdiger; Plant, Adrian; Ivković, Marija; Gattolliat, Jean-Luc (Zootaxa, 2022)
Knowledge of the European aquatic dance flies (Clinocerinae, Hemerodromiinae) is updated. The following new synonyms are proposed: Chelifera pallida Vaillant, 1981 with Chelifera diversicauda Collin, 1927, syn. nov.; Chelifera giraudae Vaillant, 1981 and Chelifera berdeni Vaillant, 1978 (nomen nudum) with Chelifera subangusta Collin, 1961, syn. nov.; Hemerodromia slovenica Horvat & Wagner, 1989 with Hemerodromia laudatoria Collin, 1927, syn. nov.; Hemerodromia maculata Vaillant, 1968 with Hemerodromia unilineata Zetterstedt, 1842, syn. nov.; Wiedemannia aerea Vaillant, 1967 with Wiedemannia hastata (Mik, 1880), syn. nov.; Wiedemannia brevilamellata Wagner, 1985 with Wiedemannia debilis Collin, 1961, syn. nov.; Wiedemannia bilobata Oldenberg, 1910 with Wiedemannia oxystoma (Bezzi, 1905), syn. nov. Lectotypes are designated for Clinocera (Wiedemannia) oxystoma Bezzi, 1905, Wiedemannia aerea Vaillant, 1967, Wiedemannia bilobata Oldenberg, 1910, Philolutra erminea Mik, 1887, Wiedemannia hastata (Mik, 1880), Wiedemannia mirousei Vaillant, 1956 and Phaeobalia pokornyi Mik, 1886. A neotype is designated for Wiedemannia alpina Vaillant, 1953. Wiedemannia rudolfi Wagner & Ivković, sp. nov. and Phaeobalia remschakae Wagner sp. nov. are described and figures of male terminalia are provided.